THE ROLE OF ETHNOECOLOGICAL CULTURE IN THE ENVIRONMENTAL ADAPTATION AND SUSTAINABLE LIVELIHOOD OF ETHNIC COMMUNITIES - Pulatova Nigora Rakhimjonovna (Sciental Journals Publishing, 2025)
Ethnoecological culture represents the unique knowledge, practices, and beliefs that ethnic communities develop through their long-standing interaction with their natural environment. This culture plays a vital role in the environmental adaptation and sustainable livelihood of these communities, helping them to survive and thrive in diverse and often challenging ecosystems. This article explores the concept of ethnoecological culture, its components, and its significance in maintaining ecological balance, ensuring food security, and preserving cultural identity.
Keywords: Ethnic communities, sustainable livelihood, ethnoecological culture, knowledge, skill, adaptation.